2018
DOI: 10.1111/cge.13441
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and phenotype analysis using an epilepsy‐associated gene panel in Chinese pediatric epilepsy patients

Abstract: Epilepsy is a common and genetically heterogeneous disorder among children. Advances in next-generation sequencing have revealed that numerous epilepsy genes, helped us improve the understanding of mechanisms underlying epileptogenesis, and guided the development of treatments. We identified 39 candidate variants in 21 genes, including 37 that were pathogenic or likely pathogenic variants according to the American College of Medical Genetics and Genomics scoring system and two variants of uncertain significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 33 publications
4
42
0
Order By: Relevance
“…We identified 29 pathogenic variants from 37 unrelated patients reported in the literature (Allen et al, ; Calhoun et al, ; de Kovel et al, ; Fitzgerald et al, ; Latypova et al, ; Marini et al, ; Miao et al, ; Parrini et al, ; Saitsu et al, ; Samanta, ; Soden et al, ; Srivastava et al, ; Thiffault et al, ; Torkamani et al, ).…”
Section: Variant Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 29 pathogenic variants from 37 unrelated patients reported in the literature (Allen et al, ; Calhoun et al, ; de Kovel et al, ; Fitzgerald et al, ; Latypova et al, ; Marini et al, ; Miao et al, ; Parrini et al, ; Saitsu et al, ; Samanta, ; Soden et al, ; Srivastava et al, ; Thiffault et al, ; Torkamani et al, ).…”
Section: Variant Spectrummentioning
confidence: 99%
“…This study provided the initial evidence of the deleterious effect of variants p.Ser347Arg, p.Thr374Ile, and p.Gly379Arg on KCNB1 function. Following the initial identification of KCNB1 variants (Torkamani et al, ), 29 new KCNB1 variants have been reported in 37 patients detected through next‐generation high‐throughput sequencing in cohorts of individuals with developmental delay and/or DEE (Allen et al, ; Fitzgerald et al, ; Saitsu et al, ; Soden et al, ; Srivastava et al, ; Thiffault et al, ; Torkamani et al, ; Calhoun, Vanoye, Kok, George, & Kearney, ; de Kovel et al, ; Latypova et al, ; Marini et al, ; Miao, Peng, Chen, Gai, & Yin, , 2018; Parrini et al, ; Samanta, ; Zhu et al, ). The majority of these patients had epilepsy, intellectual disability, and behavioral problems (MIM# 616056; epileptic encephalopathy, early infantile, 26).…”
Section: Introductionmentioning
confidence: 99%
“…Patients carrying KCNQ2 gene mutations will have benign familial neonatal seizures (BFNS), benign familial neonatal-infantile seizures (BFNIS) or benign familial infantile seizures (BFIS); they usually have benign courses even if some affected children will experience recurrent febrile seizures, benign childhood epilepsy with centrotemporal spikes (BCECTS), or photosensitive epilepsy during follow-up (2, 3, 1215). On the other side, KCNQ2 gene mutations have also been associated with early myoclonic encephalopathy (EME) and early onset epileptic encephalopathy (EOEE), such as Ohtahara syndrome (OS) and intractable partial epilepsy, characterized by poor developmental prognosis (4, 12, 13, 16, 17).…”
Section: Introductionmentioning
confidence: 99%
“…Interictal EEG is usually normal in BFNS but it shows multifocal epileptiform abnormalities, random attenuation, or burst-suppression (BS) pattern in KCNQ2-related encephalopathy: thus, a severely abnormal interictal EEG is important in the differential diagnosis between KCNQ2-related encephalopathy and BFNS (2, 11, 2123). Patients with KCNQ2-related epilepsies usually present a generalized EEG attenuation or suppression even after brief seizures (2, 17, 22, 23). Brain magnetic resonance imaging (MRI) is usually normal or shows a transient hyperintense globus pallidus (11, 23).…”
Section: Introductionmentioning
confidence: 99%
“…8). Although KCNB1 has been extensively studied, primarily in the context of epilepsy [61][62][63][64][65][66] , these studies do not include either of the two mutations identified here. These two mutations occur in the unstructured C-terminus cytoplasmic tail region of this transmembrane potassium channel protein 61,66 .…”
Section: Discussionmentioning
confidence: 99%